Personal and Cultural Nomadism in Selected Works of Contemporary Slovenian Female Fiction Writers - Borovnik, Silvija (Slavia Centralis, 2023)
The article deals with the issue of multiculturalism and interculturality in selected works by contemporary Slovenian female writers. It takes into account a tendency that has been very prominent in literary historical research in recent years, namely the need to take into account the aspect of crossing and transgressing borders and the hibridity of writers’ identities when analysing literary works. Various researchers believe that it is necessary to foster an open research attitude towards everything that has been materially and thematically, as well as linguistically different, but at the same time cohesive in Slovenian literary history. The article is based on the conviction that Slovenian literary texts are understood differently in an intercultural context and establish an interesting intertextual dialogue with many other languages and cultures.